Mechanical Characteristics of Bamboo Nanofibers Reinforced with Carbon Nanotubes via Direct Chemical Treatment of Recycled Polypropylene - Nur Iwana Irdina Othman; Md Noh, Nur Ilya Farhana; Suffiyana Akhbar; Zakiah Ahmad; Rahida Wati Sharudin; Sajith Thottabthil AbdulRahman; Bijesh Paul; Lum Wei Chen; Norshariza Mohamad Bhkari; JL Ng; Ruzaimah Razman; Mohamad Azim Mohammad Azmi; et al. (International Journal of Integrated Engineering, 2026)
Bamboo was recognized for its economic potential and historical significance in construction was being investigated focusing on its fiber as a green alternative to traditional construction materials in response to limited resources in developing countries like Malaysia. Effects of different bamboo fibers mass fraction in bamboo polymer composites (0%, 10%, 20%, and 30%) on the BF/PP/CNTs composites’ mechanical characteristics were assessed. Direct Nitric Acid Hydrogen Peroxide treatment was applied on bamboo fibers to remove lignin and hemicellulose. Employing CNTs as nanofiller in bamboo polymer composites was believed to result in better dispersion. Addition of waste polypropylene in the composites able to reduce plastic waste crisis while making its strength properties to good use. The mechanical tests revealed significant increment in tensile and flexural properties up to 20% bamboo fibers mass fraction. However, beyond the value (20% BF) in the composites, the mechanical properties of composites declined, making the composites with 20% BF became the optimum value of bamboo fibers content. Thus, this indicates BF/PP/CNTs compositions had resulted in significant improvement in the mechanical properties using treated bamboo fiber and addition of CNTs.